2022
DOI: 10.1186/s12978-022-01446-2
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Antenatal Care (ANC) services during the COVID-19 first wave: insights into decision-making in rural India

Abstract: Background Antenatal care (ANC) services are a prime focus of the Government of India's National Health Mission (NHM), of which a key pillar is the promotion of maternal and child health. To ensure uninterrupted service delivery at the last mile, a cadre of Frontline Health Workers (FLHWs) has been appointed and health centres established at the village level. However, the onset of the COVID-19 pandemic and the nationwide lockdown from late March to June 2020 impacted pregnant women's access to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
0
13
0
2
Order By: Relevance
“… 29 , 30 However, compared to our sample, utilization of maternal health services was higher in Ethiopia (64.8%) 21 and Malawi during the lockdown. 29 Elsewhere, RMNCH service utilization dipped below pre-COVID levels in India, 31 and in Pakistan, cesarean section rates (57%), hospital deliveries (37%), and postnatal visits (37%) declined. 32 Further, maternal health service utilization decreased in Haiti (18%) and Mexico during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 However, compared to our sample, utilization of maternal health services was higher in Ethiopia (64.8%) 21 and Malawi during the lockdown. 29 Elsewhere, RMNCH service utilization dipped below pre-COVID levels in India, 31 and in Pakistan, cesarean section rates (57%), hospital deliveries (37%), and postnatal visits (37%) declined. 32 Further, maternal health service utilization decreased in Haiti (18%) and Mexico during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The study findings suggest a significant financial burden on low-income households due to the high out-ofpocket expenditure with concomitant loss of wages during the pandemic. Studies from other states of India and also Africa reported the observation of a similar phenomenon [22,23].…”
Section: Discussionmentioning
confidence: 72%
“…De acordo com Bankar & Ghosh (2022), na Índia, devido aos serviços limitados, essa modalidade era a única que, em algumas situações, funcionava. Na Arábia Saudita, os médicos da família contataram as gestantes cadastradas e questionavam sobre movimentação fetal e demais queixas, com objetivo de manter um canal de acesso ao pré-natal e adesão aos planos de tratamentos e intervenções governamentais para segurança durante a pandemia (Chen et al, 2022).…”
Section: Discussionunclassified
“…A rápida mudança ou interrupção do acesso aos serviços de assistência materna em meio a divulgação de informações incompletas ou falsas nas mídias e o medo de contrair a Covid-19 assustou e interferiu na preparação para o parto e puerpério das gestantes (Bankar & Ghosh, 2022). Cerca de 50% das mulheres que tiveram filhos durante a pandemia afirmaram que o acesso às consultas de pré-natal foi dificultado pelo momento.…”
Section: Discussionunclassified